Accessibility and equity: A conceptual framework and research agenda. (October 2022) - van Wee, Bert
Abstract: This discussion paper proposes a conceptual model for the factors influencing ethical concerns regarding accessibility, building on the idea that people should have a minimum level of access to some destinations (founded in the ethical principle of sufficientarianism), and secondly from the idea that differences in levels of accessibility between (groups of) people could be relevant from an equity perspective (founded in the ethical principle of egalitarianism). The four components of accessibility introduced by Geurs and van Wee (2004) – the land use system, the transport system, the individual, and the temporal component – are included in the conceptual model which additionally disentangles the individual component, includes context factors (such as culture/religion), digital access options, perceived accessibility and normative judgments. In addition, this paper proposes a research agenda suggesting several types of quantitative and qualitative methods to study the complex relationships proposed in the model, and research to address those parts of the model for which limited knowledge is currently available. Highlights: Conceptual model accessibility and equity. Underpinnings based on sufficientarianism and egalitarianism. Disentangling of personal factors. Avenues for future qualitative and quantitative research.